eBusiness in Healthcare From eProcurement to Supply Chain Management - Hübner, Ursula; Elmhorst, Marc A. (Health Informatics, 2008)
When speaking about eBusiness as applied to the healthcare market two questions arise immediately. Firstly, what is eBusiness? Secondly, why is eBusiness in healthcare different from eBusiness in other sectors? Within the arena of eBusiness in healthcare, the focus is on purchasing and selling online as the most advanced application. In this book, the Authors consider both the perspective of the healthcare providers and that of the suppliers, showing the interdependencies between the two and developing concepts for a new synergistic cooperation. eBusiness in Healthcare raises awareness of and interest in electronically mediated business processes in healthcare to a large audience including healthcare informaticians, medical business managers, clinicians, pharmacists and scientists. By taking an international approach to the topic the authors demonstrate the many similarities of eBusiness problems and their solutions among different countries which permits analysis of the differences that are often defined by the national healthcare systems and their rules. Case studies from healthcare institutions and from suppliers in the US, the UK and Germany will illustrate the achievements, barriers and future plans, thus enabling newcomers to learn from previous experience. Clinicians will gain significant insight by this book which demonstrates the interconnection between patient care processes and management issues at the level of medical supplies. The book also makes a plea for a multidisciplinary effort, to enable the right product to be procured for the right patient. As a rather new discipline, eBusiness in healthcare needs further scientific backing. Against this background, this book will not only provide answers but will also raise questions for future research. Managing change and innovation and establishing the critical mass for eBusiness in healthcare is a major undertaking. The aim of this book is to support this process.